2015
DOI: 10.1007/s00127-015-1106-2
|View full text |Cite
|
Sign up to set email alerts
|

Disease network of mental disorders in Korea

Abstract: Therefore, major depressive disorder and nicotine dependence are highly connected to other mental disorders in Korea, indicating their comorbidity and possibility of shared biological mechanisms. The use of networks could enhance the understanding of mental disorders to provide effective mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Thirty-three studies were identified, which included 15 studies reported in the systematic review in 2013 [14]. Among the 18 included studies in this retrieval, 3 studies offered 2 or 3 groups of data: Hay 2017's study [1] was performed in 2014 and 2015, respectively; Choi 2015's study [21] was divided into KECR-R (performed in 2006-2007) and KECA-2011 (performed in 2011); and Shi 2015's study [12] showed three groups of data from Shanxi Province, Gansu Province and Henan Province in China. Hence, there were 22 groups of data in total.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three studies were identified, which included 15 studies reported in the systematic review in 2013 [14]. Among the 18 included studies in this retrieval, 3 studies offered 2 or 3 groups of data: Hay 2017's study [1] was performed in 2014 and 2015, respectively; Choi 2015's study [21] was divided into KECR-R (performed in 2006-2007) and KECA-2011 (performed in 2011); and Shi 2015's study [12] showed three groups of data from Shanxi Province, Gansu Province and Henan Province in China. Hence, there were 22 groups of data in total.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…There were 6 Chinese articles (including 3 dissertations [12,23,24]) and 13 separate English articles. Three studies were conducted in America [13,18,25]; 3 in Australia [1,26]; 1 each in Italy [22], Switzerland [17], Korea [21] and Saudi Arabia [15,16]; and 8 in China [12,23,24,[27][28][29][30][31], in which only 1 was national research [31], while the remaining 7 were regional studies limited to provinces or cities. DSM-IV and DSM-5 were used as newer diagnostic criteria than DSM-III and ICD.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Some researches reported that 50% pregnant women in Indonesia experience depression [12], and impaired mental health [13]. 2% in the world [14] have experienced mental disorder caused by anxiety and depression [15]. Although the number seems small, it actually represents a large number and this has become a big problem especially for midwives in the attempt of reducing the incidence of morbidity and mortality on pregnant women [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the lifetime prevalence of clinical ED among Korean adults (0.0% and 0.1%, respectively, for anorexia nervosa and bulimia nervosa) (Choi, Lee, Cho, Park, & Gim, ) is thought to be much lower than those among U.S. adults (0.6% and 1.0%, respectively, for anorexia nervosa and bulimia nervosa) (Hudson, Hiripi, Pope, & Kessler, ), with the ratio of 1:10 for bulimia nervosa. Nonetheless, the low prevalence of ED in Korean epidemiological studies contrasts with data from clinical samples describing prevalent ED cases in Korean women (Kim, Son, Nah, & Park, ; Thomas et al, ).…”
Section: Introductionmentioning
confidence: 99%